MYH7-related myopathies: clinical, histopathological and imaging findings in a cohort of Italian patients. Issue 1 (December 2016) - Fiorillo, C.; Astrea, G.; Savarese, M.; Cassandrini, D.; Brisca, G.; Trucco, F.; Pedemonte, M.; Trovato, R.; Ruggiero, L.; Vercelli, L.; D'Amico, A.; Tasca, G.; et al.
Abstract Background Myosin heavy chain 7 (MYH7 )-related myopathies are emerging as an important group of muscle diseases of childhood and adulthood, with variable clinical and histopathological expression depending on the type and location of the mutation. Mutations in the head and neck domains are a well-established cause of hypertrophic cardiomyopathy whereas mutation in the distal regions have been associated with a range of skeletal myopathies with or without cardiac involvement, including Laing distal myopathy and Myosin storage myopathy. Recently the spectrum of clinical phenotypes associated with mutations inMYH7 has increased, blurring this scheme and adding further phenotypes to the list. A broader disease spectrum could lead to misdiagnosis of different congenital myopathies, neurogenic atrophy and other neuromuscular conditions. Results As a result of a multicenter Italian study we collected clinical, histopathological and imaging data from a population of 21 cases from 15 families, carrying reported or novel mutations inMYH7 . Patients displayed a variable phenotype including atypical pictures, as dropped head and bent spine, which cannot be classified in previously described groups. Half of the patients showed congenital or early infantile weakness with predominant distal weakness. Conversely, patients with later onset present prevalent proximal weakness. Seven patients were also affected by cardiomyopathy mostly in the form of non-compacted left ventricle. Muscle biopsy was consistent with minicores myopathy in numerous cases. Muscle MRI was meaningful in delineating a shared pattern of selective involvement of tibialis anterior muscles, with relative sparing of quadriceps. Conclusion This work adds to the genotype-phenotype correlation ofMYH7 -relatedmyopathies confirming the complexity of the disorder.